Identificación de Materiales que cambian de fase con uso potencial para el ahorro energético en edificaciones - Brennecke Quinzo, Johana Carolina (2021)
Nowadays, the construction activity consumes 36% of the final energy demand, it is focused to space heating and cooling, 86.4% of this energy comes from non-renewable sources and is responsible for 39% of CO2 emissions. Consequently, it has been identified as an important sector to reduce these numbers through the use of renewable sources and environmentally friendly systems. This research project proposed to identify Phase Change Materials in order to reduce energy demand, the environmental pollution generated, and increase the thermal efficiency in buildings. The methodology consisted of a bibliographic review, to study the operation of these PCMs in the construction materials, a comparative energy simulation was carried out using the “PCM Express” software between a house with traditional materials versus a house with PCM. It was possible to identify certain organic PCMs as potential ones due to their characteristic and wide range of melting temperature, being in the thermal comfort parameters (18-24 °C) to be used in the construction activity. Consequently, to the above mentioned, they present certain disadvantages such as material leakage during phase change or low thermal conductivity, however, thanks to encapsulation technologies, this can be controlled and improved.